Which is better: stapler haemorrhoidopexy vs traditional excisional surgery? - Prasad Naragam, Amarendra; Kumar Tavva, Santosh; Arra, Priyanka (International Surgery Journal, 2019)
Background: Haemorrhoids are tortuous dilated veins within the submucosa of anal canal. They are external, internal or internoexternal. External haemorrhoids cause pain. Internal haemorrhoids are characterised by painless bleeding or prolapse. Various treatment options are available- dietary modification, band ligation, sclerosant therapy, cryosurgery, traditional excisional surgery (Milligan/Ferguson), stapler haemorrhoidopexy, Doppler guided haemorrhoidal artery ligation (DGHAL), application of harmonicscalpel and ligasure. Methods: Adult patients (>18 yrs) with grade II, III & grade IV haemorrhoids are randomly allotted in equal numbers to receive either stapler haemorrhoidopexy or traditional excisional surgery from July 2017 to December 2018. Post-operative complications, pain (using visual analogue scale), recurrence rate and the need for further surgery with these procedures were analysed in this 1 and half year study period. Results: Patients who underwent stapler haemorrhoidopexy had better temporary quality of life, but patients who underwent traditional excisional surgery had lesser recurrence. Conclusions: Overall, traditional excisional surgery should be the choice when compared to stapler haemorrhoidopexy.